International Perspectives on Teaching and Learning for Mathematical Literacy - Bolstad, Oda Heidi; Goodchild, Simon; Goos, Merrilyn (Educational Research E-Books Online, Collection 2024., 2025)
Mathematics plays an important role in today's world and is used in daily life more that often is appreciated. Mathematical literacy denotes the competence to deal with the mathematical issues of life in modern society. The underlying purpose of this book is to support the development of rich understandings and practices of how an education for mathematical literacy can be realised. The collected works, emerging from several educational systems, offer a fresh perspective on mathematical literacy and the chapters include practical examples that teachers, pre-service teachers, and teacher educators might adapt to their own needs.